Labor migration and its impact on economic status - Shrestha, Mohan Kumar (Innovative Research Journal, 2022)
The present study entitled Labor Migration and its Impact in Bhaktapur has been carried out with the main objective to identify the socio-economic and demographic characteristics of international labor migrants' households, This study was conducted by applying descriptive type of research by using survey based research design. International labour migration is a process which is very significant. Remittance from abroad is supporting the national economy to a great extent. Unemployment is a burning issue and foreign employment is providing employment to many from across Nepal. Foreign currency has weight and with the high exchange rate it can really be rewarding Work and Wage is mostly determined by skill, education and fluency. People are surviving and at the same time hoping that sooner or later foreign employment will be a blessing. It is just a matter of years spend abroad by the migrants that will improve the economic condition of the respective households. Level of income for migrant households has increased but expenditure also increased respectively. Standard of living and quality of food are raised of their family. Unemployment lack of agricultural land and poverty are important factors for emigration associated with origin. Likewise, high wage rate, easy availability of unskilled works and no need of higher education other important factors associated destination. Some positive and negative impacts also seem in foreign employment.